2016
DOI: 10.1007/s40858-016-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nematode assemblages and physical properties across land use types

Abstract: The purpose of this study was to determine the influence of land use types on nematode assemblage in sugarcane production in Pernambuco State, Brazil. One forest and two managed agricultural soils were characterized by their nematode assemblages to assess their biological characteristics. Soil samples were collected between 2009 and 2010 at three 10-cm depth increments along two 200-m transects with points at 20-m intervals from each other. Nematodes were extracted by sucrose centrifugation, and the physical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…e experiment included data on 3455 women who notified pregnancy between 1999 and 2012. e development of a diet-based diabetes risk score in the study aims to quantify the association between adherence to the prior diet score and the incidence of type 2 diabetes,; among the 9 food categories for which diet scores (reported to be negatively correlated with the incidence of type 2 diabetes), 3 food categories are reported to be directly related to type 2 diabetes. Donazar-Ezcurra M assessed three types of compliance with diet-based diabetes risk scores: low (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), intermediate (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and high (40-60). Compared with the lowest category, the higher category showed an independent inverse correlation with the risk of developing gestational diabetes (multivariate-adjusted OR 0•48; 95% CI 0•24, 0•99; linear trend P: 0•01).…”
Section: Introductionmentioning
confidence: 99%
“…e experiment included data on 3455 women who notified pregnancy between 1999 and 2012. e development of a diet-based diabetes risk score in the study aims to quantify the association between adherence to the prior diet score and the incidence of type 2 diabetes,; among the 9 food categories for which diet scores (reported to be negatively correlated with the incidence of type 2 diabetes), 3 food categories are reported to be directly related to type 2 diabetes. Donazar-Ezcurra M assessed three types of compliance with diet-based diabetes risk scores: low (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), intermediate (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and high (40-60). Compared with the lowest category, the higher category showed an independent inverse correlation with the risk of developing gestational diabetes (multivariate-adjusted OR 0•48; 95% CI 0•24, 0•99; linear trend P: 0•01).…”
Section: Introductionmentioning
confidence: 99%
“…Genera Criconemella, Helicotylenchus, Trichodorus, and Paratrichodorus are common in the region (Chaves et al 2003;Moura 2005;Rodrigues et al 2011;Cardoso et al 2015), though in low numbers (Spaull and Cadet 2005). The plant-parasitic nematodes are prevalent in sugarcane growing fields around the world (Berry et al 2007;Stirling et al 2010;Berry et al 2011;Steven et al 2014;Cardoso et al 2016;Zhang et al 2017) as well as in northeastern Brazil (Chaves et al 2002(Chaves et al , 2003Barros et al 2005;Vicente et al 2016). Economic damage levels are related to nematode species, sugarcane variety, and environmental conditions, especially soil humidity (Dinardo-Miranda 2005;Barros et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…juveniles per 50 g of roots of susceptible sugarcane varieties (Dinardo-Miranda et al 1996;Novaretti 1997). However, sand soils under environmental stress from water deficits are more affected by plant-parasitic nematodes (Li et al 2014;Lu et al 2016;Vicente et al 2016), disrupting the soil's natural balance and food web (Sohlenius et al 2011;Cardoso et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes activities have been suggested as sensitive indicators of soil biological properties (Dick, 1997;Nannipieri, 1994). The literature assessed showed that natural habitats have the highest enzymes' activity followed by pasture, while sugarcane presented a low enzymes' activity (Cardoso et al, 2016;Brackin et al, 2013;Ye and Wright, 2010;Sant'Anna et al, 2009;Zou and Bashkin, 1998;Magarey et al, 1997).…”
Section: Soil Biological Propertiesmentioning
confidence: 99%